Budget Impact Analysis of Darbepoetin Alfa Every 3 Weeks versus Epoetin Alfa Every Week for Cancer Patients with Anemia due to the Effect of Concomitant Myelosuppressive Chemotherapy - November McGarvey; Hairong Xu (Journal of Health Economics and Outcomes Research)
**Background:** Anemia is a common complication among patients with cancer receiving chemotherapy and can cause significant costs to health plans.